Evaluation of Geomembrane Effect Based on Mobilized Shear Stress due to Localized Sinking. (2nd May 2019) - Lu, Weihua; Zhang, Yongxing; Liu, Weizheng; Liu, Cheng; Wang, Haibo
Abstract : Installing geosynthetic reinforcement at the bottom of the embankment will provide positive support for subgrade stability and settlement control, if there is a void or a weak foundation. In routine design work, the geomembrane effect must be well estimated and the tensile strain should be precisely predicted. Conventional analytical methods often adopt the limit state method to calculate the overlying load on the deflected geosynthetic. However, this assumption does not necessarily apply to all conditions, especially when the foundation soil can provide certain resistance. In this study, a semiempirical prediction method for evaluating the geomembrane effect of the basal reinforcement was proposed, and an iterative solution for calculating tensile strains of a deflected geosynthetic was deduced. In derivation, a virtual inclined slip surface and interaction between the geosynthetic and soil were quantitatively evaluated by coupling the arching effect and the geomembrane effect. Moreover, the development of shear stress along the slip surface can be considered, as well as different segments of the basal reinforcement. Then, the proposed method was validated by two large-scale experiments. Comparison of the results of this method with measurements and results of other analytical models confirmed that this analytical method can take good care of the varying process of the localized sinking, regarding the overlying loads on the geosynthetic and the subsequent tensile strains.